Analisis Hukum terhadap Hak Imunitas Advokat Dalam Beracara Memberikan Bantuan Hukum - M Rudi Hartono; Radi Candra (Wajah Hukum, 2021)
The existence of advocates as justice seekers at this time is very much needed and important in the life of the community and nation as well as increasing legal awareness and the complexity of legal problems in society. Advocacy is a profession that provides legal services to the public or its clients who face legal problems, both those related to criminal, civil and state affairs. Legal services provided by Advocates can be in the form of legal consultations, legal assistance, legal advice providers, exercising power, representing, assisting, defending, and performing other legal actions for and on behalf of clients. In providing these legal services, an Advocate can carry out it through a prodeo (Free of charge) or obtain an honorarium or payment for services from the client. In general, the position of an advocate is equal to that of other law enforcers such as the judges, prosecutors, and the police. : "Thus, advocates also play an important role in upholding and protecting the law for the community. The proper role of an advocate has been regulated in Law Number 18 of 2003 concerning "Advocates.